2023
DOI: 10.1155/2023/5328927
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Multiomics Prediction Model for Radiation Pneumonitis

Abstract: Objective. The study aims to establish and validate an effective CT-based radiation pneumonitis (RP) prediction model using the multiomics method of radiomics and EQD2-based dosiomics. Materials and Methods. The study performed a retrospective analysis on 91 nonsmall cell lung cancer patients who received radiotherapy from 2019 to 2021 in our hospital. The patients with RP grade ≥1 were labeled as 1, and those with RP grade < 1 were labeled as 0. The whole lung excluding clinical target volume (lung-CTV) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, it also points out that severe radiation pneumonia can occur if V5 is too high, but there is currently no standard recommendation 3 . Zhou's research found that the AUC for predicting the incidence of radiation pneumonia using lung DVH is 0.801–0.804 4 . Hou's research found that the AUC for predicting the incidence of radiation pneumonia using lung DVH is 0.634 5 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it also points out that severe radiation pneumonia can occur if V5 is too high, but there is currently no standard recommendation 3 . Zhou's research found that the AUC for predicting the incidence of radiation pneumonia using lung DVH is 0.801–0.804 4 . Hou's research found that the AUC for predicting the incidence of radiation pneumonia using lung DVH is 0.634 5 .…”
Section: Discussionmentioning
confidence: 99%